Analisis Finansial Pengolahan Biji Dan Fuli Pala (Myristica fragrans Houtt) Organik (Studi Kasus Pada Home Industri Galela Jaya) Di Desa Dokulamo Kabupaten Halmahera Utara - Linda Umasugi; Haryati La Kamisi (Sangia Publishing, 2018)
Nutmeg is one of the mainstay potential export commodities of the North Maluku regional government, as a source of economic growth and regional income. To be able to maintain and enhance the role of the processing industry sector in national development, efforts are needed to determine the economic value of processed products. This study aims to analyze the processing of organic nutmeg at Galela Jaya Home Industry in Dokulamo Village, North Halmahera Regency. Analyzing financially organic nutmeg at Galela Jaya Home Industry in Dokulamo Village, North Halmahera Regency, using investment feasibility criteria, namely NPV, B/C ratio, IRR, PBP and qualitatively using seed processing and nutmeg mace. Based on the results of the analysis it can be said that the seed processing and nutmeg business carried out by the Galela Jaya Home Industry is feasible because it can provide benefits to the company, from the results of the analysis of financial feasibility at an interest rate of 9%, NPV is Rp. The amount of IDR 1 will provide a benefit of IDR 5%. The value of IRR is obtained at a value of Rp 115.16%, and the importance of the criteria for the investment return period (Playback Period) is obtained at Galela Jaya Home Industry for about 1 year.Nutmeg is one of the mainstay potential export commodities of the North Maluku regionalgovernment, as a source of economic growth and regional income. To be able to maintain and enhance the roleof the processing industry sector in national development, efforts are needed to determine the economic value ofprocessed products. This study aims to analyze the processing of organic nutmeg at Galela Jaya Home Industryin Dokulamo Village, North Halmahera Regency. Analyzing financially organic nutmeg at Galela Jaya HomeIndustry in Dokulamo Village, North Halmahera Regency, using investment feasibility criteria, namely NPV,B/C ratio, IRR, PBP and qualitatively using seed processing and nutmeg mace. Based on the results of theanalysis it can be said that the seed processing and nutmegbusiness carried out by the Galela Jaya HomeIndustry is feasible because it can provide benefits to the company, from the results of the analysis of financialfeasibility at an interest rate of 9%, NPV is Rp. The amount of IDR 1 will provide a benefit of IDR 5%. Thevalue of IRR is obtained at a value of Rp 115.16%, and the importance of the criteria for the investment returnperiod (Playback Period) is obtained at Galela Jaya Home Industry for about 1 year